Infantile Neuroaxonal Dystrophy: Diagnostic Criteria - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The diagnostic significance of clinical, neurophysiologic, and neuroradiologic findings in 13 patients with infantile neuroaxonal dystrophy (INAD) was evaluated at the National Neurological Institute, Milan, Italy.